2009
DOI: 10.1002/chem.200802602
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Uptake of COS, CS2, and SO2: Ionic Liquids with O‐Alkylxanthate, O‐Alkylthiocarbonyl, and O‐Alkylsulfite Anions

Abstract: CO(2)-binding organic liquids (CO(2)BOLs) are mixtures of a base (typically an amidine or guanidine) and an alcohol, and have been shown to reversibly capture and release CO(2) with low reaction energies and high gravimetric CO(2) capacity. We now report the ability of such liquid blends to chemically bind and release other acid gases such as CS(2), COS, and SO(2) analogously to CO(2). These systems bind with sulfur-containing acid gases to form colored ionic liquids with new O-alkylxanthate, O-alkylthiocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…During the absorption of CO 2 observed in this study, the phenolic ILs reacted with CO 2 C NMR spectrum of the product showed a new band at d = 161 ppm during the absorption of CO 2 , thereby also indicating the formation of carbonate salt. On the basis of previous reports [35,[38][39][40] and the observed reaction product, we present Scheme 2 as the absorption mechanism of CO 2 by these phenolic ILs. Thus, equimolar CO 2 capture can be achieved because these phenolic ILs react with CO 2 in a 1:1 manner.…”
Section: Ionic Liquid T [8c]mentioning
confidence: 93%
“…During the absorption of CO 2 observed in this study, the phenolic ILs reacted with CO 2 C NMR spectrum of the product showed a new band at d = 161 ppm during the absorption of CO 2 , thereby also indicating the formation of carbonate salt. On the basis of previous reports [35,[38][39][40] and the observed reaction product, we present Scheme 2 as the absorption mechanism of CO 2 by these phenolic ILs. Thus, equimolar CO 2 capture can be achieved because these phenolic ILs react with CO 2 in a 1:1 manner.…”
Section: Ionic Liquid T [8c]mentioning
confidence: 93%
“…[19,26,32,33] Interestingly, Ludwig et al found that a strong, local, and directional hydrogen bond can decrease the melting points and viscosities of ILs, and fluidize them. [34,35] Furthermore, some phenomena involving in RTILs, including low melting point (< 100 8C), measured vaporization pressure, thermal decomposition, [36] even solubility of water, capture of gases (CO 2 and SO 2 ), [8,37] dissolution of cellulose, [11] and so forth, can be explained perfectly by the hydrogen-bonded interaction.…”
Section: Introductionmentioning
confidence: 95%
“…- [7,8]. The involvement of the hydroxyl group during the chemical absorption of SO2 in DBEA was further demonstrated by 13 C NMR experiments.…”
Section: Resultsmentioning
confidence: 91%